Murmuring against Moses: the contentious history and contested future of Pentateuchal studies - Bergsma, John Sietze (Emmaus Academic, 2023)
"For much of the history of both Judaism and Christianity, the Pentateuch-first five books of the Bible-was understood to be the unified work of a single inspired author: Moses. Yet the standard view in modern biblical scholarship contends that the Pentateuch is a composite text made up of fragments from diverse and even discrepant sources that originated centuries after the events it purports to describe. In Murmuring against Moses, John Bergsma and Jeffrey Morrow provide a critical narrative of the emergence of modern Pentateuchal studies and challenge the scholarly consensus by highlighting the weaknesses of the modern paradigms and mustering an array of new evidence for the Pentateuch's antiquity. By shedding light on the past history of research and the present developments in the field, Bergsma and Morrow give fresh voice to a growing scholarly dissatisfaction with standard critical approaches and make an important contribution toward charting a more promising future for Pentateuchal studies"--